Arts-based research. Other ways of knowing and producing knowledge (Praxis Educativa, 2024)
This work seeks to generate other ways of knowing and producing knowledge, based on Susan Finley's proposal of research (and education) based on the arts. A new tool that is part of the postmodernist turn, and that we will try to frame within the methodological approach of the ethnographic field. To do this, we are going to recall the foundations of this type of work and its genealogy. From the so-called "armchair anthropologists" who turned to the field, to the present day where the modality is oriented, within the qualitative approach, not only to understand exotic cultures, but also segregated or oppressed communities. Arts-based research, we understand, is part of these changes, as opposed to the apparent systematicity of the traditional research process of science and its methodology. Incorporating the strong visceral, emotional, corporal and passionate component that identifies the human, as well as artistic expression.
Keywords: Arts-based research; postmodernist turn; ethnography; qualitative approach; fieldwork